Intellectual Capital, Islamic Corporate Social Responsibility, Enterprise Risk Management, and Financial Performance of Halal Industry Companies - Hermawan, Sigit; Amalia, Dina Ananda Nur; Arista, Sintha Wahyu; Rahayu, Duwi; Maryanti, Eny (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2025)
This study aims to determine the effect of Intellectual Capital, Islamic Corporate Social Responsibility, and Enterprise Risk Management on the Financial Performance of Halal Industry Companies Listed on the IDX. The population in this study is industrial sector companies. The sampling technique used in this study is purposive sampling. The analysis technique used in this study uses Statistical Product and Service Solutions (SPSS). Based on the results of the study, it can be concluded that Intellectual Capital, Islamic Corporate Social Responsibility, and Enterprise Risk Management have a partial effect on Financial Performance.